(untitled) (Palíndromo, 2024)
This article aims to investigate a costume design project developed for the tragedy “Othello” for the Student Theater of Brazil in 1949. The object, as a primary source, is described and analyzed with the aim of identifying formal characteristics that reveal artistic choices by Pernambuco de Oliveira, the designer responsible. As the time and space of this Shakespearean play suggests, the Venetian school of painting is indicated, particularly in Gentile and Giovanni Bellini, achieving the symbols borrowed to the drawing - in a transfer from painting to drawing and how the difference in support manifests itself. In this comparative examination, we seek to understand how the represented character takes shape, suggesting a dialogue between the visual and performing arts, capturing their similarities and visual solutions.